2017
DOI: 10.4103/ija.ija_352_17
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion index as a predictor of hypotension following propofol induction - A prospective observational study

Abstract: Background and Aims:Hypotension during propofol induction is a common problem. Perfusion index (PI), an indicator of systemic vascular resistance, is said to be predictive of hypotension following subarachnoid block. We hypothesised that PI can predict hypotension following propofol induction and a cut-off value beyond which hypotension is more common can be determined.Methods:Fifty adults belonging to the American Society of Anesthesiologists' physical status I/II undergoing elective surgery under general ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 14 publications
4
28
1
Order By: Relevance
“…In line with our findings, Mehandale and Rajasekhar [20] tested the ability of baseline PPI to predict hypotension following propofol induction of general anesthesia in 50 adult healthy patients. The study revealed a significant correlation between the baseline PPI and propofol-induced hypotension.…”
Section: Discussionsupporting
confidence: 65%
“…In line with our findings, Mehandale and Rajasekhar [20] tested the ability of baseline PPI to predict hypotension following propofol induction of general anesthesia in 50 adult healthy patients. The study revealed a significant correlation between the baseline PPI and propofol-induced hypotension.…”
Section: Discussionsupporting
confidence: 65%
“…The PI is calculated as the ratio of pulsatile to non-pulsatile signals in arterial blood flow [ 6 , 7 ]. To date, the PI has been used to predict low blood pressure [ 8 ], identify early success indicators of central and peripheral nerve blocks [ 9 , 10 ], assess pain [ 11 , 12 , 13 ], evaluate systemic vascular resistance [ 14 , 15 ], indicate the success of sympathectomy for hyperhidrosis [ 16 ], and identify the incidence of hypotension after spinal anesthesia [ 17 ]. However, few studies have investigated the correlation between the PI and body temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Propofol is a common cause of hypotension. [ 2 ] There are many studies which have explained the effect of hypotension on various organ systems and their functioning; it can present as stroke,[ 3 ] myocardial injury, or acute kidney injury in patients undergoing general[ 3 ] and cardiac[ 4 ] surgeries. Postinduction hypotension can lead to increased postoperative morbidity and mortality, as well as postoperative stay.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 ] However, propofol is known to cause hypotension. [ 1 2 5 6 ] Hypotension following propofol is due to myocardial suppression and decreased systemic vascular resistance. [ 6 ] A multimodal approach consisting of nonpharmacological and pharmacological interventions has been advocated to reduce postinduction hypotension, and assessment of inferior vena cava (IVC) diameter is one of them.…”
Section: Introductionmentioning
confidence: 99%